2020
DOI: 10.1016/j.radcr.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous hibernoma: A metastatic mimicker to consider on the differential

Abstract: Intraosseous hibernoma is an uncommon brown fat tumor that with about 2-dozen case reports described in the literature. Hibernomas are more commonly found in soft tissues of the thigh, shoulder, and back. However, more cases of intraosseous hibernomas are coming to light as a result of work-up due to pain or as an incidental lesion finding. Herein, we present a case of a thoracic intraosseous hibernoma suspicious for an isolated ovarian cancer metastasis, successfully treated with radiofrequency ablation and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
“…Intraosseous hibernomas are rarely documented, usually in the form of case reports or small series, with only 38 cases in the English language literature 8–31 . The relatively small number of reported cases limits our understanding of these tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Given the benign nature of an intraosseous hibernoma, no treatment is necessary once the condition is confirmed via histopathology. Our review of the literature identified only two patients who underwent surgical resection [ 20 , 22 ] and 2 patients who received radiofrequency ablation [ 13 , 27 ]. Consistent with the current body of literature, neither of our 2 patients required further intervention following definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first known case of an intraosseous aggregate of brown adipose tissue was discovered during a trephine bone biopsy as part of a clinical work-up for essential thrombocytopenia in 2006 [7] . Currently, only 35 total cases of intraosseous hibernomas have been reported within international literature [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Similar to their soft tissue counterparts, they are usually found incidentally while working up a different clinical scenario, although occasionally they present with pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation